Fetal exome sequencing for isolated increased nuchal translucency: should we be doing it?. (14th September 2021) - Mellis, R; Eberhardt, RY; Hamilton, SJ; ,; McMullan, DJ; Kilby, MD; Maher, ER; Hurles, ME; Giordano, JL; Aggarwal, V; Goldstein, DB; Wapner, RJ; et al.
Abstract : Objective: To evaluate the utility of prenatal exome sequencing (ES) for isolated increased nuchal translucency (NT) and to investigate factors that increase diagnostic yield. Design: Retrospective analysis of data from two prospective cohort studies. Setting: Fetal medicine centres in the UK and USA. Population: Fetuses with increased NT ≥3.5 mm at 11–14 weeks of gestation recruited to the Prenatal Assessment of Genomes and Exomes (PAGE) and Columbia fetal whole exome sequencing studies ( n  = 213). Methods: We grouped cases based on (1) the presence of additional structural abnormalities at presentation in the first trimester or later in pregnancy, and (2) NT measurement at presentation. We compared diagnostic rates between groups using Fisher exact test. Main outcome measures: Detection of diagnostic genetic variants considered to have caused the observed fetal structural anomaly. Results: Diagnostic variants were detected in 12 (22.2%) of 54 fetuses presenting with non‐isolated increased NT, 12 (32.4%) of 37 fetuses with isolated increased NT in the first trimester and additional abnormalities later in pregnancy, and 2 (1.8%) of 111 fetuses with isolated increased NT in the first trimester and no other abnormalities on subsequent scans. Diagnostic rate also increased with increasing size of NT. Conclusions: The diagnostic yield of prenatal ES is low for fetuses with isolated increased NT but significantly higher where there are additional structural anomalies. Prenatal ES may not be appropriate for truly isolated increased NT but timely, careful ultrasound scanning to identify other anomalies emerging later can direct testing to focus where there is a higher likelihood of diagnosis. Tweetable abstract: Prenatal ES has a low diagnostic rate (<2%) for isolated increased NT but is significantly more likely to yield a diagnosis where there are additional fetal structural anomalies. Linked article This article is commented on by AN Talati and NL Vora, p. 61–62 in this issue. To view this mini commentary visit https://doi.org/10.1111/1471-0528.16942 .